Effect of high-intensity sports specific training and high-intensity interval training on sprained ankle male adolescent soccer athletes before return-to-play - Yake Chen; Yonghwan Kim (Journal of Men's Health, 2023)
Ankle sprain is a highly observed injury in soccer due to repeated strenuous movements. Rehabilitation after injury leads to decreased physical strength and muscle-joint function. The ankle sprained patients need improved soccer specific fitness and ankle function simultaneously. Therefore, current study aimed to compare high-intensity sports specific training (HISST) with high-intensity interval training (HIIT) to identify effective training for fitness and lower-extremity functions. A total of 56 high school male soccer players (HIIT: 28, HISST: 28) who survived the acute phase due to ankle sprain participated the study. In the intervention period of 4 weeks, the HISST and HIIT groups were randomly assigned. Physical fitness and lower-extremity function tests were performed before and after the intervention. Physical fitness measurements included Volume Oxygen peak (VO2peak), anaerobic power, isokinetic ankle eversion strength, while lower extremity function tests consisted of Y-balance and hop tests. In both groups, VO2peak, exercise time, peak power, and eversion strength improved after the intervention, with significant improvement in all Y-balance subtests and hop tests (p < 0.05). Regarding the posteromedial and posterolateral directions of the Y-balance test, and the crossover of the hop tests, HISST was significantly higher (p < 0.05) than HIIT in the post-intervention test. Concludingly, HIIT and HISST can simultaneously improve VO<, abductor strength, and lower extremity function in sprained ankle athletes before returning to competition. Additionally, HISST was slightly more effective than HIIT for mediolateral balance and crossover hopping.